2020
DOI: 10.1093/nar/gkaa1201
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC1 cytosine deaminase activity on single-stranded DNA is suppressed by replication protein A

Abstract: Many APOBEC cytidine deaminase members are known to induce ‘off-target’ cytidine deaminations in 5′TC motifs in genomic DNA that contribute to cancer evolution. In this report, we characterized APOBEC1, which is a possible cancer related APOBEC since APOBEC1 mRNA is highly expressed in certain types of tumors, such as lung adenocarcinoma. We found a low level of APOBEC1-induced DNA damage, as measured by γH2AX foci, in genomic DNA of a lung cancer cell line that correlated to its inability to compete in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 96 publications
3
24
0
Order By: Relevance
“…It is well established that non-B DNA structures cause replication stalling and require special systems aiding to replicate these regions 34 . This could lead to higher recruitment of replication protein A (RPA), which binds to ssDNA and is known to counteract APOBEC deamination 35,36 . An alternative or an additional explanation could be recruiting for replicating of non-B DNA regions the specific DNA polymerase called Primase-Polymerase (PrimPol).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that non-B DNA structures cause replication stalling and require special systems aiding to replicate these regions 34 . This could lead to higher recruitment of replication protein A (RPA), which binds to ssDNA and is known to counteract APOBEC deamination 35,36 . An alternative or an additional explanation could be recruiting for replicating of non-B DNA regions the specific DNA polymerase called Primase-Polymerase (PrimPol).…”
Section: Discussionmentioning
confidence: 99%
“…Further exploration is necessary to find efficient and specific Ades in addition to those tested in this study. In addition to virus-derived Ades, it has been reported that single-stranded binding proteins, small-molecule inhibitors and chemically modified oligonucleotides can suppress the cytosine deaminase activity of APOBEC deaminases 60 65 . These potential antagonists of deaminases merit further exploration to develop new inhibitors of CBEs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that non-B DNA structures cause replication stalling and require special systems aiding to replicate these regions ( Wang and Vasquez, 2017 ). This could lead to higher recruitment of replication protein A (RPA), which binds to ssDNA and is known to counteract APOBEC deamination ( Brown et al., 2021 ; Wong et al., 2021 ). An alternative or an additional explanation could be recruiting for the replicating of non-B DNA regions the specific DNA polymerase called Primase-Polymerase (PrimPol).…”
Section: Discussionmentioning
confidence: 99%